Announcement - The 2009 Paper Award of Tribology Online - - Masabumi Masuko (Japanese Society of Tribologists, 2010)
The Japanese Society of Tribologists is pleased to announce that the 2009 Paper Award of Tribology Online was awarded to:“Development of Three-Dimensional Non-Contact Surface Profilometer and Application of Impact Erosion of Metal Matrix Composites,” by Yoshiro Iwai, Masato Kitasho, Eisuke Sentoku, Tomomi Honda, Toru Matsubara and Kazuhisa Yanagi, Vol. 3, No. 1 (2008) 19-24.The Award Medals were presented to the authors by Dr. Hisashi Machida, the former President of the Japanese Society of Tribologists, at the Annual Meeting on 18th May, 2010.